A Fixed Point, A Point of Interruption - Hewson, Mark (Cosmos and History: The Journal of Natural and Social Philosophy, 2006)
A review of Alain Badiou, Infinite Thought: Truth and the Return to Philosophy, ed. and trans. Justin Clemens and Oliver Feltham, New Edition, London, Continuum, 2005. ISBN: 0826479294.